Effectiveness of the arbuscular mycorrhizal fungi use in the cherimoya (Annona cherimola Mill.) seedlings growth - William Viera; Diego Campaña; Salomé Castro; Wilson Vásquez; Pablo Viteri; José Zambrano (Acta Agronómica)
Cherimoya (Annona cherimola Mill.) is native to the inter-Andean valleys of southern Ecuador and northern Peru. In Ecuador, the yield of this fruit crop is low, mainly due to agricultural management problems and poor fertilization. This research aims to assess the effect of native mycorrhizal fungi on seedling growth of cherimoya (cultivar 'Cangahua'). Sampling of soil and roots was carried out in 14 production sites of cherimoya. Soils that obtained the largest number of spores and greatest percentage of mycorrhizal colonization were those collected in Tumbabiro (plot 10), Gonzanamá, Paute and San Francisco de Atahualpa. These soils were used to propagate the inoculums in trap plants (Sorghum vulgare) and subsequently, they were used to inoculate the seeds and seedlings of cherimoya. There was no statistical difference to jointly analyze the results obtained in the inoculated seeds and seedlings. However, independently, the inoculum coming from the soil of Tumbabiro obtained the best results by doubling the content of total phosphorus and 47% increase in dry matter in cherimoya seedlings compared to control.